Bridging the gaps in eating disorder care: a systematic and comparative review of guidelines for prevention, early intervention, and service delivery - Monaco, Francesco; Vignapiano, Annarita; Landi, Stefania; Panarello, Ernesta; Pullano, Ilaria; D’Angelo, Martina; Longobardi, Anna; di Gruttola, Benedetta; Di Stefano, Valeria; Malvone, Raffaele; Ferrara, Agnese; Marenna, Alessandra; et al. (Frontiers in Psychology, 2025)
BackgroundEating Disorders (EDs) pose a significant public health challenge due to their psychiatric and somatic complexity, high chronicity, and elevated mortality rates. Despite the growing body of evidence and international awareness, the quality and consistency of clinical guidelines remain variable.ObjectiveThis systematic review aimed to evaluate and compare existing clinical guidelines and position papers addressing prevention, early intervention, and multidisciplinary treatment for EDs.MethodsA systematic search of PubMed and American Psychological Association (APA) PsycINFO was conducted for documents published between January 2015 and March 2025. Eighteen documents were included, encompassing formal guidelines, consensus statements, and national policies. Key domains were extracted and synthesized across documents. Quality was assessed using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) tools.ResultsSubstantial convergence was found in the emphasis on nutritional rehabilitation, psychological therapy, and medical monitoring (87.5, 87.5, and 81.3% of guidelines, respectively). Stepped-care models and multidisciplinary approaches were frequently endorsed but unevenly operationalized. In contrast, recommendations on pharmacotherapy (37.5%) and prevention strategies (43.8%) were less consistently addressed. Major gaps included the lack of standardized criteria for care levels, limited guidance on comorbidity management, and underrepresentation of recovery-oriented models. Notably, Italy lacks a centralized national guideline for EDs.ConclusionThis review highlights both commonalities and critical divergences in current ED guidelines. The findings underscore the need for international harmonization, clearer implementation tools, and stronger integration of early intervention and recovery frameworks. These insights can inform future policy development, clinical training, and service reorganization to improve outcomes and equity in ED care.